Dora d’Istria et le printemps des peuples du Sud-Est Européen - Ileana Mihăilă (Revista de Istorie și Teorie Literară)
It is a new look and approach on the works of Dora d’Istria, a Romanian writer in French language, which contributions realize a deeper knowledge about South-Western peoples of Balkans These contributions are very few known and the author try to disseminate it to a larger public.